2018
DOI: 10.21873/anticanres.12592
|View full text |Cite
|
Sign up to set email alerts
|

An Agonistic Antibody to EPHA2 Exhibits Antitumor Effects on Human Melanoma Cells

Abstract: Abstract. Background/Aim: EPH receptor A2 (EPHA2) is highly expressed in aggressive types of human cancer, and is expected to be an excellent target molecule for antibody treatments. In this study, we investigated the therapeutic potential of antibody to EPHA2 against melanoma in vitro. Materials and Methods: We generated three monoclonal antibodies (mAbs) to EPHA2 and examined cell-surface expression by flow cytometry. To investigate the ability to inhibit tumor cell migration therapy with mAbs to EPHA2, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…Decreased ligand-mediated receptor internalization and degradation, consequently enhancing protein stability, might help increase EphA2 amounts in malignant cells. An interesting consequence of EphA2 stimulation (by ligand or antibody) is EphA2 phosphorylation, internalization, and degradation [43][44][45]. After liganddependent induction, EphA2 aggregation occurs at the cell surface, followed by tyrosine phosphorylation, In the malignant state, loss of cell-cell contacts induces receptor-ligand interaction and degradation of EphA2.…”
Section: Epha2 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased ligand-mediated receptor internalization and degradation, consequently enhancing protein stability, might help increase EphA2 amounts in malignant cells. An interesting consequence of EphA2 stimulation (by ligand or antibody) is EphA2 phosphorylation, internalization, and degradation [43][44][45]. After liganddependent induction, EphA2 aggregation occurs at the cell surface, followed by tyrosine phosphorylation, In the malignant state, loss of cell-cell contacts induces receptor-ligand interaction and degradation of EphA2.…”
Section: Epha2 In Cancermentioning
confidence: 99%
“…Indeed, treatment with D2 scFv induced apoptosis and reduced cell proliferation in the lymphoma cell line. In addition, Sakamoto et al [43] showed that one of the EphA2 mAbs produced, SHM16, interacts with an EphA2 epitope differing from that affecting ephrin A1 binding to EphA2. SHM16 was clearly internalized in cells and inhibited malignant features in melanoma cells.…”
Section: Soluble Ephrin A1 and Ephrin A1-fcmentioning
confidence: 99%
“…Accumulative clinical evidence has demonstrated that Eph receptors expression is associated with clinicopathological parameters important for patient management and prognosis in a variety of tumors [ 13 , 14 , 15 , 16 , 17 , 18 ]. Among others, there are reports about the role of Eph receptors in skin melanomas [ 19 , 20 ]. However, there is no comprehensive available data concerning the clinical significance of Eph receptors expression in uveal melanoma, whose biology is significantly different from skin melanomas.…”
Section: Introductionmentioning
confidence: 99%
“…26 Its downregulation and neutralization of the encoded protein have been associated with decreased migration and invasion of melanoma cells indicating its role in oncogenesis. 27,28 Epha2 knockout mice exhibit a greater susceptibility to chemically induced skin cancer, which suggests a tumor suppressor function of this gene, and its overexpression in tumor cells a likely compensatory mechanism to decrease cell proliferation. 29 Regardless of the mechanism, EPHA2 is involved in skin cancer.…”
mentioning
confidence: 99%